Politician as the Leader in Indonesia’s Student Regiment and Its Psychological Impacts - Indro Adinugroho; Hobby Putra Anky (Jurnal Studi Pemerintahan, 2020)
It has been a long debate that politicians should not be involved in any organizations which has a primary purpose to educate civil society. Indonesia student regiment (Menwa) is an example of the organization which functions as a vessel for Indonesian students to encourage engagement in the field of national defense and tri-dharma, a responsibility to give contributions while students in university. However, for over 6 years, Menwa has been led by a politician who also becomes an active board in a political party. Considering the basic function of Menwa, ethically Menwa should be led by a professional without any political interest to keep maintaining the purity of the purpose. Despite its negative impact, there is also a positive consequence. Politician who becomes a leader in the organization can share political knowledge and value to the members to become active citizens, particularly enhance the political participation of its members. This study aims to identify a relationship between supporting politician as the leader and three aspects of psychological orientation towards politics (POTP). Result shows that members who support the leader (politician) tend to have higher scores in political efficacy (PE) and political interest (PK), two fundamental variables which are needed in democratic country than the other groups.